Regional Differences in End-Diastolic Volumes between 3D Echo and CMR in HLHS Patients - Gomez, Alberto; Oktay, Ozan; Rueckert, Daniel; Penney, Graeme P.; Schnabel, Julia A.; Simpson, John M.; Pushparajah, Kuberan (Frontiers in Pediatrics, 2016)
Ultrasound is commonly thought to underestimate ventricular volumes compared to Magnetic Resonance Imaging (MRI), although the reason for this and the spatial distribution of the volume difference is not well understood. In this paper, we use landmark-based image registration to spatially align MRI and ultrasound images from patients with Hypoplastic Left Heart Syndrome and carry out a qualitative and quantitative spatial comparison of manual segmentations of the ventricular volume obtained from the respective modalities. In our experiments, we have found a trend showing volumes estimated from ultrasound to be smaller than those obtained from MRI (by approximately up to 20 ml), and that important contributors to this difference are the presence of artefacts such as shadows in the echo images and the different criteria to include or exclude image features as part of the ventricular volume.